Developing Instructional Media for Vocational School Students - Rawis, Joulanda A.M.; Jacobus, Susan N H; Dondokambey, Clay J H; Sauyai, Stanly F M; Qowi, Moh.; Kalesaran, Renaldy J (JR Education, 2023)
Technology in the field of education can now be utilized with the aim of solving various existing problems, including students' learning problems at school. The aim of this research is to develop interactive learning media in network service technology subjects at Christian Vocational School 1 Tomohon as a tool in the learning process. The development method used is the Multimedia Development Life Cycle (MDLC) method. This development method consists of 6 stages, namely: (1) Concept, (2) Design, (3) Material Collecting, (4) Assembly, (5) Testing, (6) Distribution. This learning media testing includes 3 tests, namely compatibility testing by media experts, material suitability testing by material experts, and usability testing by users. Making this learning media itself uses the Adobe Animate application. From the tests that have been carried out, the results show that interactive learning media in the network service technology subject at Christian Vocational School 1 Tomohon has no problems and is suitable for use as a tool for students and teachers in the learning process.